Solar Drying for Value Addition and to Minimize Post-harvest Losses - Ofor, M O; Nwufo, M I; Ibeawuchi, I I (Annals of Arid Zone, 2016)
Agriculture p~od~cehave b,eentraditionally dried in the open sun for their consumption ~unng off-season. ~rymg IS,eSS,entIal,to prevent spoilage due to micro-organisms. Drying I~ the ~pen results m contammatIon WIth dust and after discoloration of the produce. Natural CIrculatIon solar dryers have been effectively used to dehydrate the farm produce. Some case stud~e~ vegetables, spices, condiments and fruit are discussed. The solar drying for value addItIon and proper packaging of the dried l'roducts to enhance shelflife are highlighted. Key words: Solar drying, solar dryers, processing for drying, nutritional value of dried products, packaging: